Calibration of the temporal drift in absolute and relative Raman intensities in large Raman images using a mercury–argon lamp. (28th September 2021) - Jakubek, Ryan S.; Fries, Marc D.
Abstract: Raman imaging is a powerful tool for the analysis of astromaterials including meteorites, cosmic dust, and samples returned to Earth by spacecraft. Many astromaterials are heterogeneous on mm‐ or cm‐sized scales requiring the collection of large Raman images with long accumulation times of days to weeks. It is known that the wavenumber and bandwidth calibration of a Raman instrument drifts with time and temperature resulting in significant changes in the observed Raman band over the course of Raman image collection. In this work, we examine the temporal and thermal drift of absolute and relative Raman intensities through the collection of a Raman image. We show that the spectrometer throughput and observed Raman intensities change over time and are correlated to small changes in lab temperature. We propose a method of calibrating for the drift in Raman intensities using a Hg–Ar (mercury–argon) calibration lamp integrated into the Raman instrument. We also show that relative Raman intensities drift with time as a function of temperature as a result of changes to the Raman instrument response function. We developed a method to calibrate the drifting instrument response function using only the calibration lines from the Hg–Ar lamp. Overall, our results elucidate the effects of temporal/thermal drift on Raman intensities and we propose calibration techniques to account for these effects. Abstract : In this work we examine the temporal drift in absolute and relative Raman intensities in Raman images. We find that the absolute intensities and wavelength dependent instrument response function drifts temporally. We propose a method of calibrating Raman images to account for this temporal drift using a Hg–Ar calibration lamp.